Analysis of modern air transportation in Russia - T. A. Petrova; V. A. Kardanov (Вестник университета)
Modern air cargo transport is an important part of global logistics and trade. They provide fast and efficient delivery of goods all over the world. In recent years, there have been several significant changes in the development of air routes both in the Eurasian Economic Union (hereinafter referred to as EAEU), and in Russia, in particular. Additionally, in light of recent global events such as the COVID-19 pandemic, air cargo has faced additional challenges related to restrictions on passenger flights, changes in airport operating hours and increased health regulations, while the geopolitical situation has had a significant impact on transport and development of transport infrastructure throughout the EAEU. All these challenges make this study relevant. In addition, the article examines the rules of law that regulate issues of economic and customs space, as well as solve the problems of applying bans on customs duties and other restrictions on the free movement of goods, services and financial resources. Ways have been proposed to overcome restrictions on air transportation within the framework of the EAEU.